Nirmatrelvir treatment of SARS‐CoV‐2‐infected mice blunts antiviral adaptive immune responses - Valeria Fumagalli; Pietro Di Lucia; Micol Ravà; Davide Marotta; Elisa Bono; Stefano Grassi; Lorena Donnici; Rolando Cannalire; Irina Stefanelli; Anastasia Ferraro; Francesca Esposito; Elena Pariani; et al. (EMBO Molecular Medicine)
Abstract Alongside vaccines, antiviral drugs are becoming an integral part of our response to the SARS‐CoV‐2 pandemic. Nirmatrelvir—an orally available inhibitor of the 3‐chymotrypsin‐like cysteine protease—has been shown to reduce the risk of progression to severe COVID‐19. However, the impact of nirmatrelvir treatment on the development of SARS‐CoV‐2‐specific adaptive immune responses is unknown. Here, by using mouse models of SARS‐CoV‐2 infection, we show that nirmatrelvir administration blunts the development of SARS‐CoV‐2‐specific antibody and T cell responses. Accordingly, upon secondary challenge, nirmatrelvir‐treated mice recruited significantly fewer memory T and B cells to the infected lungs and mediastinal lymph nodes, respectively. Together, the data highlight a potential negative impact of nirmatrelvir treatment with important implications for clinical management and might help explain the virological and/or symptomatic relapse after treatment completion reported in some individuals.